2016
DOI: 10.3390/recycling1030311
|View full text |Cite
|
Sign up to set email alerts
|

Drywall (Gyproc Plasterboard) Recycling and Reuse as a Compost-Bulking Agent in Canada and North America: A Review

Abstract: The incessant disposal of drywall waste, generated predominantly from construction and demolition sites, has been associated with many environmental problems. In landfill sites, it has long been linked with the generation of hydrogen sulphide, a toxic and foul-smelling gas, while the incineration of this waste results in the potential release of sulphur dioxide gas, a contributor to acid rain formation. The traditional disposal methods also result in the loss of a valuable resource. Therefore, proper managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Gypsum drywall, also known as wallboard or sheetrock, is a widely used construction material that is composed of 93% calcium sulphate dihydrate and 7% paper (Gypsum Association, 2023). In Canada, waste drywall accounts for about 9% of the mass of waste generated from construction and demolition waste streams (Ndukwe & Yuan, 2016). The annual production, construction, and demolition of plasterboards worldwide generate approximately 15 million tons of gypsum waste that could be repurposed for this soil health initiative (ReportLinker, 2021).…”
Section: Overview/main Goalmentioning
confidence: 99%
See 1 more Smart Citation
“…Gypsum drywall, also known as wallboard or sheetrock, is a widely used construction material that is composed of 93% calcium sulphate dihydrate and 7% paper (Gypsum Association, 2023). In Canada, waste drywall accounts for about 9% of the mass of waste generated from construction and demolition waste streams (Ndukwe & Yuan, 2016). The annual production, construction, and demolition of plasterboards worldwide generate approximately 15 million tons of gypsum waste that could be repurposed for this soil health initiative (ReportLinker, 2021).…”
Section: Overview/main Goalmentioning
confidence: 99%
“…The recycling of gypsum from drywall waste would provide a sustainable long-term solution that reduces the amount of construction waste that ends up in landfills. Approximately 496,000 to 585,000 tons of drywall waste is generated annually in Canada (Ndukwe & Yuan, 2016). Over the past few years, this number has continued to rise due to population and economic growth (Ndukwe & Yuan, 2016).…”
Section: Long-term Impactsmentioning
confidence: 99%
“…ft.) generates a metric ton of gypsum board waste, and a 50,000 sq. ft. office building generates~16 metric tons of waste [20]. According to the Centers for Disease Control and Prevention (CDC), drywall sanders are exposed to as much as 10 times the permissible exposure limit of 15 mg/m 3 for total dust set by the Occupational Safety and Health Administration (OSHA) [21].…”
Section: Introductionmentioning
confidence: 99%
“…Questions have also been raised about the disposal of gypsum board in landfills. The sulfate component of the gypsum board can be degraded by sulfate-reducing bacteria (anerobic microorganisms), which produce toxic levels of hydrogen sulfide gas [20,23]. This gas is flammable and hazardous, and could lead to severe health problems.…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that the mechanical performance of the recycled plasterboard is similar to the original product. Ndukwe and Yuan (2016) have provided a detailed review of recycling options for gypsum materials in Canada and North America. They have reported potential recycling options such as a core material for plasterboard production, a soil amendment to add nutrients to soil, a bulking agent to compost materials, a cement additive to control setting time, in wastewater treatment to settle suspended clay particles in the treatment process, a manure treatment to reduce odour, in animal bedding to absorb moisture, grease absorption, in sports fields to draw lines, as dental molds and in roadways to facilitate leaching of salts from soil.…”
Section: Introductionmentioning
confidence: 99%